Analysis of acoustic field distribution of circular equaldistant and non-equidistant two–section electronics microphone array in free space - Тsekhmistro, R.I.; Shapovalov, S.V. (Radiotekhnika, 2023)
The authors described the analysis of the spatial distribution of the acoustic field amplitude of circular microphone lattice. A model – a spherical wave emitter, represented each microphone. An analysis was carried out of the influence of the number of emitters and the radius of the array on the concentration of the acoustic field in the center and at an arbitrary distance. An algorithm has been compiled that makes it possible to take into account an arbitrary even and odd number of emitters located along the length of the arc, both uniformly and unevenly. The distribution of the complex power of the acoustic field of a linear array of emitters is considered under the assumption that each microphone (emitter) transmits the acoustic field in the form of a spherical wave. According to the classical principles (Lorentz lemma, the “Reciprocity” theorem), we believe that there is no shape of the radiation pattern as formed at short distances (near zone), that is, the distribution of the emitter field in the mode of receiving and transmitting an acoustic signal is identical. It is shown that at distances between the boundaries of the intermediate and far zones, local areas may appear in which a smaller number of microphones can provide the same acoustic field or even more than with a larger number. This can be achieved by using an internal arc of microphone arrangement, then it is possible to achieve an equivalent field along the axis of the array with a smaller number of microphones located equidistant along the outer radius, it is possible to achieve an equivalent field than with an increased number of them.